Advances in Encapsulations for Perovskite Solar Cells: From Materials to Applications. Issue 7 (2nd February 2023) - Shi, Yating; Zhang, Fei
Abstract : The poor stability hampers the commercialization of perovskite solar cells (PSCs). Many methods have recently been reported to enhance their stability, among which encapsulation is one of the most effective methods to improve the stability of PSCs. Herein, a summary of the factors influencing the stability of PSCs is provided and the commonly used encapsulation technologies and different types of encapsulation materials in detail are introduced. Then, the characterization technologies of encapsulation and stability tests of encapsulated PSCs are proposed. Finally, current issues and chances for encapsulating material development are considered. Abstract : Herein, the factors affecting the stability of perovskite solar cells (PSCs) are analyzed and the encapsulations are divided into inner encapsulation and outer encapsulation based on the encapsulation materials' location and function. Then, the classification and application of encapsulation materials are systematically summarized. In addition, the encapsulation techniques, the characterization technologies, and stability tests of encapsulated PSCs are also proposed.